EFEKTIVITAS KAMPANYE PROGRAM BOGOR TANPA KANTONG PLASTIK DALAM MEMBANGUN KEPEDULIAN MASYARAKAT PADA LINGKUNGAN - Fierda Ayu Utami; Dwi Rini Sovia; Layung Paramesti Martha (Jurnal Penelitian Sosial Ilmu Komunikasi, 2020)
This research aims to identify the influence of individual characteristics of people in East Bogor district and the effectiveness of the campaign program Bogor Without Plastic Bag to the community's concern on the environment. This study uses a descriptive quantitative approach, which is conducted in the House of residents in the Ciliwung River basin of East Bogor subdistrict. The results of research based on T test showed that there is no influence between the individual characteristics of the community of Bogor Timur (X1) consisting of age, gender, occupation, education, ethnic, and long stay in Bogor to concern Society in the Environment (Y), except on gender indicator, especially women shows have a partial influence on environmental concern. Meanwhile, based on the effectiveness program campaigns of Bogor without plastic bags (X2) significantly affects the Community's awareness on the environment (Y). The F test result indicates that the variable (X1) and (X2) affect the stimulant of the variable (Y). Result of the calculation of coefficient of determination (R2) of 47.8%, meaning not only the individual characteristics factor of the community and the effectiveness of the Bogor program without plastic bags that affect the Community's awareness of the environment.